Growth and yield of macadamia nut intercropped with irrigated Arabica coffee - Perdoná, Marcos José; Martins, Adriana Novais; Suguino, Eduardo; Soratto, Rogério Peres (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this study was to evaluate the growth and yield of macadamia nut (Macadamia integrifolia) cultivars in an intercropped system with irrigated coffee (Coffea arabica). The experiment was carried out in a completely randomized design with ten replicates. Six macadamia cultivars, from which three Brazilian (IAC 4‑12B, IAC 4‑20, and IAC 9‑20) and three Hawaiian (HAES 344, HAES 660, and HAES 816) ones were used. In the first four years of production, evaluations were done for: plant height, canopy and stem diameter, number of nuts per plant, nut average weight, almond medium weight, nut production per plant, recovery rate, and almond production per plant. The Brazilian cultivars, especially IAC 4‑20, showed a lower height, but with a larger canopy diameter. The Brazilian cultivars are more productive, among which IAC 4‑12B is outstanding.
Keywords: Coffea arabica; Macadamia integrifolia; intercropping; nut; plant size